Market Success of Premium Product Innovation: Empirical Evidence from the German Food Sector. - Kevin T. McNamara; Christoph R. Weiss; Antje Wittkopp (Kiel University, Department of Food Economics and Consumption Studies, 2003)
It is well documented that a large share of new products does not survive their first year in the market. Research reported in this paper examined the relationship between product quality and innovation success. In contrast to existing product innovation literature that focused on industrial goods, this study used food product data from a 2002 German food manufacturing firm survey. Results of Sample Selection Model suggest that premium quality increases product's success rate. Furthermore, firm size has a significant positive impact on success rate. Intensity of competition as well as retailers? market power reduce product?s success rate.
Keywords: 330; Product success; innovative behaviour; premium product quality; sample selection; German food industry; Nahrungsmittel; Innovation; Erfolgsfaktor; Produktqualität; Nahrungsmittelgewerbe; Schätzung; Deutschland